The annulus: composition, role and importance in sperm flagellum biogenesis and male fertility - Marjorie Whitfield (Basic and Clinical Andrology)
Abstract The annulus is an electron-dense ring structure that surrounds the axoneme and compartmentalizes the sperm flagellum into two parts: the midpiece and the principal piece. The function of the annulus as a diffusion barrier in the mature spermatozoon is now well described but its function during spermiogenesis remains unclear. The intriguing spatio-temporal dynamics of the annulus during spermiogenesis and its position at the interface of the two main flagellar compartments have been highlighted for more than 50 years, and suggest a major role in this process. During the last decade, numerous studies contributed in establishing a repertoire of proteins known to be located at the annulus. Mutant mouse models of invalidation of these proteins have provided essential information and clues for novel hypotheses regarding the functions and regulation of this structure. Importantly, the recent identification in humans of homozygous mutations of genes coding for annulus proteins and leading to sterility have reinforced the importance of this ring structure for sperm physiology and male fertility. This review provides a comprehensive description of all the knowledge obtained in the last several years regarding the annulus composition and functions, both in mice and in humans.